Exploring Medium- and Long-Term Respiratory and Functional Sequelae in Young Adults Post-COVID-19 - Büşra Ülker Ekşi; Eylül Pınar Kısa; Özge Ertan Harputlu; Begüm Kara Kaya; Zeynep Hoşbay; Buket Akıncı (Medicina)
Background and Objectives: Long COVID-19 syndrome may cause difficulties in functionality during daily life in young people. Our objective was to investigate the respiratory and functional sequelae in young adults with asymptomatic or mild COVID-19 compared with healthy peers 3–6 months and 6–12 months after COVID-19 infection. Materials and Methods: Participants aged 18–25 who had COVID-19 within the last 3–6 months (Post-COVID Group 1, n = 25) and 6–12 months (Post-COVID Group 2, n = 25) and age–gender-matched healthy controls (n = 25) were included in this study. Respiratory functions and muscle strength were measured. Physical function was assessed with 6 min walking test (6MWT) and an Incremental Shuttle Walk Test (ISWT). The 1 min sit-to-stand test (1-MSTST) and hand grip strength (HGS) were used to assess muscle performance. Fatigue and dyspnea severity were questioned. Results: The FVC%pred (p = 0.023) and MEP (p = 0.034) were higher, and 1-MSTST repetitions were lower in Post-COVID Group-1 compared to Post-COVID Group-2 (p = 0.029). The PEF%pred (p = 0.025), MEP (p = 0.001), and ISWT distance were lower in Post-COVID Group-2 compared to healthy controls. The number of 1-MSTST repetitions and 6MWT distance were lower in Post-COVID Group-1 (p = 0.003, p = 0.001) and Post-COVID Group-2 (p = 0.003, p = 0.017) than in healthy controls. Exercise-induced blood lactate change during the ISWT, HGS, fatigue, and dyspnea were not significantly different between post-COVID groups and healthy controls. Conclusions: Young adults who pass asymptomatic or mild SARS-CoV-2 infection exhibit a decline in FVC%pred, PEF%pred, lower extremity muscle performance, and physical function within 3–6 months. In addition, the deterioration in respiratory and physical functions becomes apparent within 6–12 months.